Validating the Traditional Chinese version of the Epilepsy Anxiety Survey Instrument (EASI) in Hong Kong - Terry K. W. Chan; Mimi M. C. Wong (Frontiers in Neurology, 2025)
BackgroundAnxiety disorders are common and have a substantial impact on people with epilepsy (PWE). However, they often go under-recognized. In recent years, epilepsy-specific anxiety has gained increasing attention in the literature. To improve mental health care for people with epilepsy (PWE), we developed and validated the traditional Chinese versions of the Epilepsy Anxiety Survey Instrument (EASI) and its brief screener (brEASI) among PWE in Hong Kong.MethodWe developed the TC-EASI through forward and backward translation, followed by a review by an expert panel and a focus group. We tested the instrument among PWE aged 18 years and older using the Chinese Bilingual version of the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (CB-SCID), which is the gold standard for diagnosing anxiety disorders. We examined the internal consistency and the test-retest reliability of the TC-EASI and TC-brEASI. We performed confirmatory factor analysis (CFA) to assess the factor structure of the TC-EASI. We also examined convergent and divergent validity using the Generalized Anxiety Disorder 7-item scale (GAD-7), the Neurological Disorders Depression Inventory for Epilepsy (NDDI-E), the Depression Anxiety Stress Scales 21 (DASS-21), and the Liverpool Adverse Events Profile (LAEP). Furthermore, we analyzed the receiver operating characteristics (ROC) of the TC-brEASI.ResultsWe included 203 Chinese PWE; 19.7% had at least one current anxiety disorder, 7.4% had a panic disorder, and 5.9% had agoraphobia without panic disorder. Both internal consistency and test-retest reliability were satisfactory. The TC-EASI revealed two latent constructs: epilepsy-specific anxiety and typical anxiety. Convergent and divergent validity were established. A cut-off score of ≥9 for the TC-brEASI yielded a sensitivity of 89.2% (95% CI = 79.2–99.2%), a specificity of 82.5% (95% CI = 76.8–88.3%), and an area under curve (AUC) of 0.925 (95% CI = 0.887–0.964).ConclusionThe traditional Chinese versions of the EASI and brEASI are reliable and valid epilepsy-specific measures.